Randomized trial of transcutaneous auricular vagus nerve stimulation on patients with disorders of consciousness: A study protocol - Cheng, Lijuan; Sun, Lingxiu; Xu, Lu; Zhao, Falin; Liu, Xiaochen; Wang, Anqi; Di, Haibo; Cong, Yu-Sheng (Frontiers in Neurology, 2023)
Background: The potential effectiveness of taVNS in the course of consciousness recovery has been highlighted by recent studies with brain injury patients. However, the underlying mechanisms of taVNS in the recovery of consciousness is not clear. Based on consciousness recovery and taVNS mechanisms, the Vagal Cortical Pathways model has been proposed. This model aims to explain the potential therapeutic effects of taVNS on brain activity in the process of consciousness recovery. Using double-blinded, cross-over design, randomized controlled trial, this study attempts to investigate the effectiveness of taVNS in DOC by means of Coma Recovery Scale-Revised (CRS-R), neuroimaging (structure MRI, fMRI), electrophysiology (EEG, ERP) and Single Molecular Array (Simoa). The primary goals of the project are three-fold: 1) evaluate the behavioral effects of taVNS, 2) explore the neural mechanisms underlying taVNS action using multi-modeling measures (within the framework of the Vagal Cortical Pathways model), and 3) identify biomarkers that correlate with responsiveness of consciousness using neurophysiology, brain imaging or biomarkers. This multi-modal project would provide insights in our understanding the mechanistic action of taVNS in consciousness recovery. Methods/design: Nighty patients with DOC acquired brain injury are randomized into one of three groups receiving sham taVNS or active taVNS (just left and left or right), respectively. The intervention period in each of the three groups will last 40 days (every 10 days for a small period, baseline 2 weeks, intervention 2 weeks, 40 min per day, 5 days per week, then no intervention for 2 weeks, intervention 2 weeks, 40 min per day, 5 days per week). Primary outcomes (Coma Recovery Scale-Revised (CRS-R)) will be recorded five times during every period from the first to the fourth. Secondary outcomes will be recorded at baseline and at the end of the fourth week (MRI,EEG, P-tau, NFL). Adverse events and untoward effects will be notes during each treatment. Discussion: This protocol presents an objective design for a randomized controlled trial that aims to study the effectiveness of taVNS therapy for DOC acquired brain injury, evaluate its safety, and explore effective therapeutic methods.